NEUROMUSCULAR ACTIVATION OF TRUNK MUSCLES DURING SIT-UP EXERCISES WITH AND WITHOUT AB ROLLER (Fiep Bulletin - online, 2014)
Different sit-up techniques with and without special devices are practiced in fitness studios and rehabilitation clinics in order to strengthen the trunk muscles and to increase the stability of the trunk. Partial and oblique sit-ups with and without devices are applied for esthetic and therapeutic purposes. The aim of this study was to compare the neuromuscular innervation pattern of the trunk's muscles (m. rectus abdominis, m. obliquu externus, m. erector spinae), m. rectus femoris and the m. sterocleidomastoideus of two sit-up exercises, the partial and cross crunch sit-up, with and without the use of a roller. Six male with mean age of 22,3 + 4,3 years, body mass 75,16 + 9,6 kg and body height of 1.72 + 0.04 m, performed 2 series with 20 repetitions of each exercise. The EMG signals were measured by bipolar surface electrodes. Ten contractions of each muscle were choice to be analyzed to each abdominal exercise. To save, filter and rectify the collected data used The DasyLab 5.0 software. The beginning and end of each innervation for the m. rectus femoris, m. obliquu externus and m. rectus abdominis was determined by the intensity of the signal's noise during rest period. The activity of m. sterocleidomastoideus e m. erector spinae was not interrupted by a rest period which made it, concentric and eccentric phases were distinguished by the duration (frequency) of each movement cycle. The data normalization was calculated by the average of the subject's RMS and PA within each muscle group. There aren't differences of innervation patterns of partial sit-up and cross crunch sit-up if they are executed with or without ab roller. Significant differences could only be identified between cross crunch sit-up with and without ab roller concerning the peak innervation of m. sternocleidomastoideus and m. obliquu externus.
Keywords: Electromyography; abdominal exercises; muscle abdominal